De pé na encruzilhada. Por uma cartografia contra-colonialista. - Joviano Gabriel Maia Mayer (2020)
This work starts from knowledges crossed by cartographic activist’s theory and practice. It is based on orality and inspired by the counter-colonialist perspective, as Nêgo Bispo teaches. It affirms counter-narratives against the colonialism, working from the modus pedalandi experienced at the rolezinhos de bike (bike rides) throughout common spaces that compose this confessional-polyphonic-narrative, resulting from transcribed orality. Along the way, there are housing squats, especially Dandara; Mofuce (Student House Association); Parque JA (Jardim América); Espaço Comum Luiz Estrela (Luiz Estrela Common Space); Santa Tereza and Kilombo Souza. All of these territories appear as expressive and symbolic fights at the heart of the city-company, which makes Belo Horizonte an interesting case for thinking about contemporary ways of resisting and building autonomous alternatives that can enhance the quilombist counterattack (Beatriz Nascimento, Lélia Gonzáles and Abdias Nascimento) against the white-patriarchal-colonialist supremacy (Bell Hooks). They are also important precedents of the fights for the right to the city, which reveal other possible ways of fighting against the colonial deterritorialization inherent in the spatial production logic of the capitalist city. The reassert of the colonialist project, with its material and symbolical strokes, associated with the fascism established in Brazil, demands a posture of transgression, commitment, boldness and creativity to produce unprecedented feasibles (Paulo Freire) and overcome this extreme situation characterized by the genocide of the Afropindoramic people (necropolitics, epistemicide) and environmental destruction. Is this, therefore, a (co)investigation that seeks how to do it? It is about how to re-exist cartographically, especially in times of scalpel guerrillas and disenchantment. For achieving this goal, the text opens up itself to a free experimentation, sharings and crossings of ancestral voices and knowledges based on transcribed conversations with Pai Ricardo de Oxóssi (Casa de Caridade Pai Jacob do Oriente/MG), Sarah Marques (Caranguejo-Tabaiares/PE), Glaucia Cristine (Kilombo Souza/MG) and Nêgo Bispo (Kilombo Saco-Curtume/PI). This manuscript also contains other oral forms, such as interviews, lectures, text-performance, letter and poetry. It is necessary to have hope and keep high the axé. Crisis always opens spaces for new opportunities, cracks where we can swing (Luiz Rufino), practice intercessions (Muniz Sodré), engagement as a love-task (Conceição Evaristo) and transgression to rewrite the future and achieve real independence. A crossways is the navel of the world. Therefore, we started from this crossway as a territory of energetic confluence (Cidinha da Silva), power and movement.